2015
DOI: 10.3390/w7052184
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Eutrophic Lake to the River Downstream: Spatiotemporal Algal Composition Changes and the Driving Factors

Abstract: Algal blooms have been frequently found at the upper reaches of the Tanglang River, which is downstream from the eutrophic Dianchi Lake. The eutrophic lake upstream is considered to be a potential source of phytoplankton, which contributes to the development of harmful algal blooms in the river downstream and can cause many serious problems for the river ecology. However, few studies focused on these kinds of rivers. Therefore, a field observation and laboratory analysis were conducted in this study. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…We observed that the variability of some environmental factors also had a significant influence on the temporal stability of phytoplankton ( Figure 7). The temporal stability of phytoplankton had a unimodal relationship with both NH 4 + -N and TP, a negative relationship with TN, and no relationship with WT, DO, and pH. The variability of these variables had little influence on the average total biomass of phytoplankton ( Figure 8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We observed that the variability of some environmental factors also had a significant influence on the temporal stability of phytoplankton ( Figure 7). The temporal stability of phytoplankton had a unimodal relationship with both NH 4 + -N and TP, a negative relationship with TN, and no relationship with WT, DO, and pH. The variability of these variables had little influence on the average total biomass of phytoplankton ( Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…There were significant differences of TN in the four seasons (one way ANOVA: F (3, 548) = 11.8, p < 0.001), with mean concentrations in the spring and winter being significantly higher than those in the summer and autumn (all p < 0.01 by post hoc Tukey HSD). Average values of NH 4 + -N ranged from 0.15 ± 0.07 mg/L in January 2013 to 3.24 ± 2.40 mg/L in December 2012. There were also apparent variations of NH 4 + -N in the four seasons (one way ANOVA: F (3, 548) = 8.9, p < 0.001), with mean concentrations in the winter and spring being significantly higher than those in the summer and autumn (all p < 0.05 by post hoc Tukey HSD).…”
Section: Variations Of Environmental Factors and Phytoplankton Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…Large lakes and reservoirs represent a very important hydro-morphological modification factor inside a stream network in terms of nutrient balance and algal growth [21]. The large reservoirs situated in the mountainous upstream parts of both the Someşul Mic and Mare subcatchments were absent from these two alternatives.…”
Section: Evaluation Of Management Alternativesmentioning
confidence: 99%